2018
DOI: 10.1021/acs.orglett.8b00720
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Aliphatic Potassium Acyltrifluoroborates (KATs) from Organocuprates

Abstract: A one-step synthesis of aliphatic KATs from organocuprates is reported. Organolithium and organomagnesium reagents were readily transmetalated onto Cu(I) and coupled with a KAT-forming reagent to yield the respective aliphatic KAT. The protocol is suitable for primary, secondary and-for the first time-tertiary alkyl substrates. These protocols considerably expand the range of KATs that can be readily accessed in one step from commercially available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…All showed quantitative conversions with no detectable starting material or deprotected KAT intermediate (see Supporting Information ). If desired, the deprotected KATs could be isolated after the photodeprotection step by removing the solvent in vacuo after addition of aqueous KHF 2 and treating the crude material in a similar fashion to the synthesis of KATs [46–48] . For our purposes, the isolation and purification was not necessary, as the KATs were anchored to an insoluble scaffold ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…All showed quantitative conversions with no detectable starting material or deprotected KAT intermediate (see Supporting Information ). If desired, the deprotected KATs could be isolated after the photodeprotection step by removing the solvent in vacuo after addition of aqueous KHF 2 and treating the crude material in a similar fashion to the synthesis of KATs [46–48] . For our purposes, the isolation and purification was not necessary, as the KATs were anchored to an insoluble scaffold ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Dumas, Bode and co‐workers reported that KATs can be synthesized by lithiation of benzotriazole‐based N,O‐acetals, followed by a trapping using a boron electrophile, and quenching with aqueous KHF 2 (Scheme A, a) ,. Bode and co‐workers also developed a thioformamide‐derived reagent that enables one‐pot KAT synthesis from aryl lithium or alkyl cuprate compounds (Scheme A, b) ,. Although these two approaches are practical, given that various N,O‐acetals or organometallic reagents are accessible from the corresponding aldehydes or halides, the requirement for highly reactive organolithium reagents still leaves room for improvement of the functional‐group tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, the scope of their original method was broadened to allow the synthesis of alkyl-substituted KATs ( Scheme 4 , entry 1). 12 If following the same procedure as published for aryllithiums, 9e double addition to the precursor was observed with their alkyl counterparts. This was probably due to the smaller size of alkyl chains, whereas an aryl group prevented the second addition by its steric bulk.…”
Section: Recent Advances In Synthesis Of Acylboranesmentioning
confidence: 99%